Safety of contrast-enhanced ultrasound using microbubbles in human pregnancy: A scoping review - Dassen, Sophie; Monen, Loes; Oei, Guid; Mischi, Massimo; van Laar, Judith (Ultraschall in der Medizin - European Journal of Ultrasound, 2024)
Successful placentation is crucial for fetal development and maintaining a healthy pregnancy. Placental insufficiency can cause a variety of obstetric complications. Despite the many efforts to enhance diagnosing placental insufficiency, no imaging technique has proven satisfactory. A promising imaging technique is contrast-enhanced ultrasound (CEUS) using microbubbles which has proven capable of (micro)vascular imaging. Its use for placental vascularization assessment in human pregnancies remains constrained by limited evidence and safety concerns. This scoping review aims to demonstrate the safety of CEUS used in human pregnancy in the published literature to date.A systematic search using PubMed, Medline, Embase, and Cochrane databases was performed. All studies where contrast-enhanced ultrasound was used in pregnant humans were included. Studies, where there was a planned termination of pregnancy, were excluded. To assess the safety of CEUS during pregnancy, relevant outcomes were divided into the following 3 categories; fetal outcome, maternal outcome, and pregnancy and neonatal outcomes.A total of 13 articles were included, in which 256 women underwent CEUS during pregnancy. No clinically significant maternal or fetal adverse events or negative pregnancy or neonatal outcomes associated with CEUS were described.Based on our findings, we consider expanding the knowledge of this promising diagnostic technique in future larger clinical studies to be safe and relevant.
Keywords: ultrasonography; contrast-enhanced ultrasound; microbubbles; safety; pregnancy